Stylistics of Vocative Case Usage in Mathnawi Ma'navi and Daftar-e Haftom - Mohammad Shadrooymanesh; Mahnaz Najafi (مطالعات زبانی و بلاغی)
Among the works attributed to Mowlana, Daftar-e Haftom (the Seventh Book) is more popular and important. The present study was conducted to investigate one of the most common stylistic features found in Mathnawi and Daftar-e Haftom. Given the wide usage of the vocative cases in Mathnawi and Daftar-e Haftom, and attributing this book to Mowlana, the present study sought to conduct a stylistic comparison of addresses, similarities, and differences between the two works in using vocative case. Since sentences with vocatives are speech-oriented, various applications of addresses by the poet would help identify perspectives, attitudes, and personal styles. Results of the present study indicated that Mowlana has been more successful in communicating with the audience and inducing his message using rhetorical methods and literary tools. However, the composer of Daftar-e Haftom failed to achieve much success in this regard, despite his efforts in creating stylistic poems.